Research of carrier mobility in NPD through negative differential susceptance spectra. Issue 3 (12th December 2014) - Xu, Hui; Tang, Chao; Zhai, Wen-Juan; Liu, Rui-Lan; Rong, Zhou; Fan, Qu-Li; Huang, Wei
Abstract : In this paper, the hole carrier mobility of organic semiconductor N, N′-diphenyl-N, N′bis(1, 1′-biphenyl)-4, 4′-diamine (NPD) was researched by negative differential susceptance spectra (− ΔB  = − w ( C  −  C geo ) ~  f ). Under the condition of space charge limited current (SCLC), through solving the drift current equation and Poisson equation and simulating the spectra − ΔB  = − w ( C  −  C geo ) ~  f, the relationship between the peak of − ΔB  = − w ( C  −  C geo ) ~  f spectra ( 1 /ƒp  = τp ) and the transfer time of carrier ( τ dc ) could be achieved to be τ dc  =  k  ×  τ p . So the hole-only device of ITO/NPD/Ag was fabricated to determine the capacitance spectra, and through which its − ΔB  = − w ( C  −  C geo ) ~  f could be plotted. According to the relationship of τ dc  =  k  ×  τ p, where k was determined to be 0.56, the transfer time and further the carrier mobility could be obtained. The carrier mobility depended on the electric field according to Poole-Frenkel model was further investigated in this report.